PENGARUH AKUNTABILITAS, TRANSPARANSI, DAN PENGAWASAN TERHADAP KINERJA ANGGARAN BERKONSEP VALUE FOR MONEY PADA INSTANSI PEMERINTAH KOTA SURAKARTA - Barokah Sitta Dewi; Paulus Theodorus Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2023)
The purpose of this study is to ascertain the partial and concurrent effects of Accountability, Transparency, and Supervision on Value for Money Conceptualized Budget Performance in Surakarta City Government Agencies.The administration of structural work units in the Regional Apparatus (PD) of Surakarta City, which amounted to 27 PDs and included 20 Departments and 7 Regional Agencies, became the population of this study. Three financial administration employees from PDs of Surakarta City Government totaling 81 people became the sample and respondents in this study. These individuals held positions such as Head of PPK (Financial Administration Officer), Head of the Finance or Administration and General Subdivision, Treasurer, Planner or Budgeting, Financial Administrator, and/or Financial Staff. In order to gather primary data for this study, surveys were used to distribute questionnaires. Before gathering study information, the questionnaire underwent validity and reliability tests. Traditional assumption tests, such as normality tests, multicollinearity tests, and heteroscedasticity tests, were the testing methods employed in this work. Both statistical and descriptive analytic techniques were used in this study. The research was carried out using the IBM SPSS Statistics 26 application.According to the findings, the factors of responsibility, openness, and supervision had an impact on budget performance and the idea of value for money at the same time. The performance of the value for money concept budget is somewhat effected by the transparency variable. While the concepts of value for money and responsibility and oversight have a substantial impact on budget performance.